PEMAHAMAN PESERTA DIDIK TENTANG BULLYING DI SMP NEGERI 25 PADANG - Ardianto, Vori - (Bimbingan dan Konseling, 2014)
Problem studied based on phenomenon in the field, there are the action of students SMPNegeri 25 Padang doing a violence repeated to other students, namely bullying. The purpose ofthis problem study was describ: 1. Understand of leaner about directly bullying. 2. Understand oflearner about indirectly bullying. This problem study was like quantitative descriptive researchthat describing about what happen really. The population of the problem study was all of SMP N25 PADANG student amount 750 people. The techniques of take sample was stratified randomsampling, take sample from each grade level, there are VII, VII, IX Class amount 88 people. Theinstrument used was a questionnaire and for data analysis was used percentage techniques. Resultof the study revealed that understanding of learners about bullying generally respondentunderstood criteria, And found the understood of learner still less with not understand enough tothe some aspects, there were understanding about bullying, seen to directly physical contact,indirect nonverbal attitude and cyber bullying.